Phylogeography and systematic revision of the Egyptian cobra (Serpentes: Elapidae: Naja haje) species complex, with the description of a new species from West Africa - Trape, Jean-François; Chirio, Laurent; Broadley, Donald G.; Wüster, Wolfgang (Zootaxa, 2009)
We use a combination of phylogenetic analysis of mtDNA sequences and multivariate morphometrics to investigate the phylogeography and systematics of the Egyptian cobra (Naja haje) species complex. Phylogenetic analysis of mitochondrial haplotypes reveals a highly distinct clade of haplotypes from the Sudano–Sahelian savanna belt of West Africa, and that the haplotypes of Naja haje arabica form the sister group of North and East African N. h. haje. Multivariate morphometrics confirm the distinctness of the Arabian populations, which are consequently recognised as a full species, Naja arabica Scortecci. The Sudano-Sahelian populations are also found to represent a morphologically distinct taxon, and thus a separate species, which we describe as Naja senegalensis sp. nov. The new species differs from all other members of the N. haje complex by a combination of colour pattern and scalation characteristics (especially higher numbers of scale rows around the neck), and the possession of a unique clade of mtDNA haplotypes. The distribution of the new species includes savanna areas of West Africa, from Senegal to western Niger and Nigeria.